2020
DOI: 10.1007/s00595-020-02169-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional assessment and surgical outcomes in very elderly patients undergoing pancreaticoduodenectomy: a retrospective study

Abstract: Background Con icting data on the safety of pancreaticoduodenectomy (PD) for elderly patients exist. Therefore, this study aimed to evaluate and compare the nutritional factors and clinical outcomes of PD between elderly and non-elderly patients. Methods A retrospective study of 122 consecutive patients who underwent PD from April 2008 to April 2020 was conducted. Preoperative and postoperative nutritional factors (prognostic nutritional index [PNI]), complication rates, and survival rates were compared betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Utsumi et al [ 7 ] evaluated long-term changes in nutritional status over one year after PD, which revealed that elderly patients had significantly lower albumin levels than their non-elderly counterparts, suggesting that elderly patients might face a prolonged recovery period and be at risk of malnutrition. Conversely, this study did not reveal differences in nutritional indicators, including albumin and PNI values, between the elderly and non-elderly groups over a two-year postoperative follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utsumi et al [ 7 ] evaluated long-term changes in nutritional status over one year after PD, which revealed that elderly patients had significantly lower albumin levels than their non-elderly counterparts, suggesting that elderly patients might face a prolonged recovery period and be at risk of malnutrition. Conversely, this study did not reveal differences in nutritional indicators, including albumin and PNI values, between the elderly and non-elderly groups over a two-year postoperative follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…With advancements in surgical techniques and perioperative care, PD is increasingly recognized as safe and effective for pancreatic ductal adenocarcinoma (PDAC), even among the elderly [ 2 , 3 , 4 , 5 , 6 ]. However, PD, a highly invasive pancreatic resection technique, has prompted numerous discussions concerning its suitability and significance for elderly patients with pancreatic cancer [ 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%